A Comparative In Vivo Study of Tissue Reactions to Four Suturing Materials - Shahla Kakoei; Fahimeh Baghaei; Shahriar Dabiri; Masoud Parirokh; Sina Kakooei (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2010)
INTRODUCTION: The purpose of this study was to compare the histopathologic reaction of four suturing materials: silk, polyvinylidene fluoride (PVDF), polyglycolic acid, and catgut in the oral mucosa of albino rabbits. MATERIALS AND METHODS: The twenty-one male mature albino rabbits which were used in this study were randomly divided into three groups of seven each. Silk, PVDF, polyglycolic acid and catgut suture materials were tested in the oral mucosa of these animals. The animals were sacrificed 2, 4, and 7 days after suturing. Two pathologists evaluated the samples by determining the presence and level of inflammation, granulation tissue, and fibrosis formation. Data were statistically analyzed by Kruskal Wallis and Mann-Whitney U tests. RESULTS: Histological features of the samples showed that PVDF and plain catgut suture materials produced more fibrous tissue (favorable response) on the fourth day in comparison with silk suture (P=0.02). Also, in the 7-day samples PVDF sutures produced the mildest inflammation when compared with the silk sutures (P=0.015). CONCLUSION: According to the results of this study, it can be convey that PVDF suture materials created mild tissue reactions and can be a reasonable candidate for suturing oral tissues.